A severe diarrhoeal outbreak in a remote Pacific island community, Anuta Island, Solomon Islands, April-June 2019 - Adam Craig; Samuel Manu; Rolly Viga; Cynthia Joshua; Jane Saepioh; Alison Sio (James Cook University, 2020)
Context: Solomon Islands is a small developing island state located in the south-western Pacific Ocean. A population of approximately 680 000 people live on more than one-third of the 992 islands that make up the country. Approximately 80% of the population reside in rural areas, many in remote, difficult to reach and poorly serviced island settings. Issue: In May 2019, the national surveillance system detected a rumour of a severe diarrhoea outbreak in a very remote and isolated community on Anuta Island, located halfway between the Solomon Islands archipelago and Tuvalu. This communication reports on the investigation and response to the outbreak, which affected 50 people (attack rate of 21.5%) and caused four deaths (case fatality rate of 8%). The authors highlight the system challenges faced in mounting the response and provide suggestions that may help overcome them. Lessons learned: The outbreak highlighted the challenges in detecting and responding to outbreaks in remote and rural areas of the Pacific Islands, and the limitations of rumour surveillance as a relied-upon surveillance strategy. The outbreak emphasises the need to build local capacity to detect, report and respond to outbreaks and the need for policy frameworks that ensure remote communities receive adequate health protection services.